The Relationship Between ICS LABA Administration and Blood Eosinophil Levels in COPD Patient at USU General Hospital - Deneuve, Olivia Monica; Pradana, Andika; Tarigan, Amira P (Journal of Society Medicine, 2024)
Introduction: Blood eosinophil count may predict treatment response in patients  with chronic obstructive pulmonary disease (COPD) during acute exacerbations. However,  the ability of blood eosinophil counts in stable status to predict eosinophilic. Method: This was a cohort retrospective study performed Juni-August 2022 to Juni-August 2023. Subject were COPD patients who were treated at the outpatient using ICS LABA therapy. Blood samples measured blood eosinophil levels first and control. Results: Based on Wilcoxon test test, there was a significant positive positive correlation of eosinophil counts between ICS LABA  Administration and Blood Eosinophil Levels in COPD Patient at USU General Hospital. Conclusion: We demonstrated association between ICS LABA Administration and Blood  Eosinophil Levels in COPD Patient (p value = 0.02).